Statistical Methods and Software for the Multilevel Social Relations Model. Issue 4 (November 2020) - Koster, Jeremy; Leckie, George; Aven, Brandy
The multilevel social relations model (SRM) is a commonly used statistical method for the analysis of social networks. In this article and accompanying supplemental materials, we demonstrate the estimation and interpretation of the SRM using Stat-JR software. Multiple software templates permit the analysis of different response types, including binary, counts, and continuous responses.